2014
DOI: 10.1002/lary.24741
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular suppressants after canalith repositioning in benign paroxysmal positional vertigo

Abstract: Vestibular suppressants significantly reduced residual symptoms compared to both placebo and no medication after CRP. However, there was no significant reduction in DHI score compared with the control group, suggesting that the residual symptoms could not be evaluated by DHI score alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 25 publications
(61 reference statements)
0
33
0
Order By: Relevance
“…Even if the DHI scores (total and for each subscale) did not show a substantial difference, they found that the residual symptoms where significantly lower in the medication group, suggesting that this type of medication could be helpful in preventing RD. 53 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the DHI scores (total and for each subscale) did not show a substantial difference, they found that the residual symptoms where significantly lower in the medication group, suggesting that this type of medication could be helpful in preventing RD. 53 …”
Section: Resultsmentioning
confidence: 99%
“…Another limit in using DHI is that it does not include specific questions about lightheadness or mild headache often complained by patients after the clinical resolution of BPPV. 53 …”
Section: Resultsmentioning
confidence: 99%
“…In terms of treatment, most of studies report that elderly patients with BPPV are more difficult to treat [7,8,[23][24][25]. There are several possible explanations for difficulty in resolving BPPV in these patients.…”
Section: Discussionmentioning
confidence: 95%
“…The authors suggested that older adults, because of a significantly higher recurrence rate, should have additional education to minimize the potential morbidity of their falls. Residual symptoms such as lightheadedness or a floating sensation after a successful repositioning maneuver can occur in up to 57% of individuals . A controlled, randomized trial demonstrated that a vestibular suppressant (dimenhydrinate) administered after canalith repositioning produced significantly greater control of residual symptoms than nonmedically treated control and placebo groups, although as noted above, caution must be exercised in older adults, because treatment with dimenhydrinate may produce anticholinergic effects and confusion.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%